Neutron Transport in Radiography - Wyman, Robert Douglas (My University, 1984)
A frequently important source of image degradation in diagnostic radiography series from the scattering of radiation within the object itself. The research presented in this dissertation is directed towards the elucidation of this source of radiographic image degradation.
The physical context selected is the passage of collimated thermal neutrons through an object of radiographic interest while the mathematical context is that of neutron transport. The analytical and computational methods are selected to emphasize the macroscopic image degradation effects of object scattering. Accordingly, isotropic neutron scattering and thermal one-group neutron-nucleus macroscopic cross-sections are employed as characterizations of the relevant interaction physics. Calculations and experiments undertaken pertain primarily to homogeneous objects of plunar geometry.
The conceptual basis of this dissertation is divided into two domains.
First, the transport of a collimated neutron beam through an object is modelled in isolation to the image formation domain with the goal of estimating the extent of object scattering that occurs. This is accomplished initially for a one dimensional homogeneous infinite slab object using a one-group integral transport formulation based on the point source diffusion kernel. An original solution to this particular form of the integral neutron transport equation is developed featuring the exact specification of a build-up factor function based on the forward partial neutron current and admitting an arbitrary degree of multiple scattering.
Additionally, an original extension to the double Pℯ method for solving the one-group integro-differential neutron transport equation is developed for calculating the two-dimensional transport of collimated neutrons through a rectangular object.
The second approach involves calculating the distribution of object scattered neutrons on the image formation plane thereby quantifying the incurred image degradation. This is accomplished by incorporating both problem domains into a system transfer function framework, involving the calculation of scattering based spatially variant point and line spread functions which are applied in the response determination for a homogeneous knife-edged slab object. Applications to the location of edges and corners on blurred neutron radiographs are established. These should ultimately be useful in the accurate radiographic dimensioning of nuclear fuel pins.
One significant result of these calculations is the quantitative evaluation of scattering based distortions that have previously been noted in neutron radiographic edge responses. The existence and relative magnitude of this phenomenon has been confirmed here using an analog Monte Carlo simulation. Experimental tests using the neutron radiography facility at the McMaster Nuclear Reactor have also been undertaken. Each of these confirmation techniques suggests that this scattering based edge distortion may possess merit as a neutron beam diagnostic indicator.
In summary, image degradation attributable to object scattering has been quantitatively examined and clarified for thermal neutron radiography. Applications in the interpretation of radiographic responses are thereby enhanced.
Keywords: Nuclear Engineering; Nuclear Engineering